Toward Political Changes: Transnational Advocacy Network for Gendercide Issue in the People’s Republic of China - Amalia, Ndaru Rizqa; Azizah, Nur (Universitas Muhammadiyah Yogyakarta, 2019)
This article examines the activism process in the People’s Republic of China-(PRC) by substantial local civil state actors and local Non Governmental Organizations (NGOs) in eradicating the custom of gendercide. Gendercide, which determines as gender-based genocide was getting worse after the adoption of the One-Child Policy in 1970s. Thus, this research tries to explain Chinese NGOs advocacy process in building the Transnational Advocacy Networks (TANs) to deliver the case of gendercide in the PRC using the ‘Boomerang Pattern’. Besides analyzing the role of local NGOs, the authors also examine the United Nations (UN) and the European Parliament, hand in hand with the United States (US) as the state actor which involves in the advocacy process. The finding of this research are: 1) Domestic NGOs have carried out numerous actions against the Chinese government by filling the lawsuit of forced abortion to the court and protection by giving a safe house for pregnant women; 2) TANs is created when the domestic NGOs build a network with other INGOs to advocate this gender-based genocide in the PRC; 3) INGOs force the United States, the UN and the member in European Parliament to response the PRC’s government by giving a condemn. As a result, these advocacy works can affect the gendercide policy though influencing the Chinese government’s process of decision making. The policy changed into ‘two-child policy’ from ‘one-child policy’.Keywords: gendercide, transnational advocacy networks, People’s Republic of China.